The Study of Strategic Flexibility Effect on Knowledge - Ghorban-Bakhsh, Raheleh; Gholipour-Kanani, Yousef (International Review of Management and Marketing, 2018)
This paper is to study effects of strategic flexibility on knowledge management. Statistical population includes 212 managers and employees in Ghalamchi, the Educational and Cultural Center. Sample size is determined to be 136 using the Morgan table, and the sampling is done through simple random sampling method. Given its objectives, the present study is an applied research classified as descriptive survey in terms of the method employed for gathering data. The questionnaire's reliability measured through Cronbach's alpha is 0.96. Results of data analysis using linear regression show that strategic flexibility has significant effect on the knowledge management. Moreover, it is revealed that strategic flexibility affects aspects of knowledge management significantly so that the strategic flexibility produces the most and least effect on knowledge acquisition (0.515) and knowledge organization respectively. Keywords: Strategic flexibility, Knowledge management, Knowledge creation, knowledge acquisition, Knowledge dissemination, JEL Classification: D8